MENGELOLA KEGIATAN PRAPEMBELAJARAN SEBAGAI UPAYA MENCIPTAKAN PROSES BELAJAR YANG KONDUSIF DI SEKOLAH DASAR NEGERI 3 SIMPANG KATIS BANGKA BELITUNG - Ocktavia, Fara Dillah (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2020)
Opening in learning is a definite activity, the mention of opening learning is a pre-learning activity or also called pre-instructional. The main function of pre-learning activities is to start learning in order to be effective which allows students to follow the learning process well. The research method used in this research is descriptive qualitative method. This method is used because in this study describing or describing the implementation of pre-learning activities. Data collection techniques in this study were carried out through interviews, observation and documentation. From the series of observations of the pre-learning activities that have been carried out at SD Negeri 3 Simpang Katis, the results of the pre-learning activities and the pre-learning habituation carried out systematically in the implementation by the class teacher, among others, before entering the class, students are advised to line up in front of the class, then shake hands with class teachers, and carry out examination of the neatness and hygiene of students. After entering the class they do literacy first, such as praying, attend students, sing Indonesian Raya songs, other national songs, memorize short chapters, and memorize multiplication. Then the class teacher can start with small games like ice breaking about movements and songs so that they can increase the enthusiasm of students to learn.